2013
DOI: 10.1007/s00792-013-0534-8
|View full text |Cite
|
Sign up to set email alerts
|

Haloferax chudinovii sp. nov., a halophilic archaeon from Permian potassium salt deposits

Abstract: Three pigmented strains of halophilic archaea (RS75, RS77, RS79) were isolated from the monoliths of mottled sylvinite from the Verkhnekamsk salt deposit (Solikamsk, Russia). The cells were nonmotile, gram-negative, pleomorphic, disk-shaped or ovoid, 0.8-1.0 × 1.5-2.5 μm. The organism was a chemoorganotrophic obligate aerobe producing catalase and oxidase. A number of carbohydrates and carboxylic acids were used as growth substrates. Growth occurred in the presence of 7-27% NaCl (with the optimum at 15-18%), 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…This critical view has not changed, since contamination issues are being suspected and an age of millions of years for a viable microorganism is difficult to imagine. From the 1990s onward, sequences of small ribosomal RNA (16S rRNA) genes and, increasingly, full taxonomic descriptions of cultivated isolates revealed novel species of Haloarchaea in ancient rock salt [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. There is now a growing body of evidence that halophilic prokaryotes, many of them Haloarchaea, are able to survive in rock salt, most likely within brine-filled fluid inclusions [ 13 , 16 , 17 , 18 ], for very long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…This critical view has not changed, since contamination issues are being suspected and an age of millions of years for a viable microorganism is difficult to imagine. From the 1990s onward, sequences of small ribosomal RNA (16S rRNA) genes and, increasingly, full taxonomic descriptions of cultivated isolates revealed novel species of Haloarchaea in ancient rock salt [ 1 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. There is now a growing body of evidence that halophilic prokaryotes, many of them Haloarchaea, are able to survive in rock salt, most likely within brine-filled fluid inclusions [ 13 , 16 , 17 , 18 ], for very long periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoid-based plumage coloration occurs through a mechanism involving carotenoid transport to blood and uptake by follicle cells in feathers 1 50 51 52 . Analysis of the major carotenoid pigments of haloarchaea 21 22 23 24 25 29 revealed that the isoprenoid-derived carotenoids, bacterioruberin and its precursors, are present in the haloarchaea membrane, giving rise to the characteristic bright pinkish-red color.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have characterized haloarchaeal diversity using culture-independent 6 7 and culture-dependent 8 9 10 11 12 13 14 15 16 17 18 approaches. These extremophilic microorganisms require an NaCl concentration of at least 1.5 M for proliferation, with optimal growth observed at 3.5–4.5 M 19 20 , and produce red or pink carotenoid pigments, including bacterioruberin 21 22 23 24 25 .…”
mentioning
confidence: 99%
“…In particular, these organisms can grow in locations with salinities ranging from 10% to 37%, pH values between 4 and 12, and temperatures between 0°C and 60°C (1). For instance, H. chudinovii grows at a pH of 6.8, 42°C, and 16% salinity (2). Halophilic species, which are resistant to dehydration, exhibit low levels of cellular macromolecule denaturation and high thermal stability (3).…”
Section: Genome Announcementmentioning
confidence: 99%